Analisis Wacana Kritis Model Norman Fairclough dalam Berita “Ketua Harian PSI Ahmad Ali Minta Kader Jaga Image Jokowi dan Kaesang” Pada Kompas.Com - Lukman Alfaris; Hari Bakti Mardikantoro; Rustono Rustono (Universitas Muhammadiyah Tapanuli Selatan, 2025)
This study aims to uncover how language is used as an ideological instrument and a means of reproducing power in political reporting in the mass media. The focus of the study is directed at a critical discourse analysis of the news